An Algorithm for Encrypted Cloud Communication - S Iyer, Sanketh; Dand, Hiren; Patil, Rajendra (International Journal of Computer Sciences and Engineering, 2025)
Internet has assumed control over everything a rapid pace. With the growth of Internet, we tried to discover way through which we can exploit the internet to the fullest and reap its benefits. Cloud Technology was a result of such brainstorming. With Cloud, we could achieve great deal of benefits. This included access to our resources anytime, anywhere and at a very fast pace. This made the task of various organizations very easy as they could store data over these cloud servers and access them from anywhere at any time. Furthermore, this also brought down the costs for the organization, as they need not invest in creating data centers and servers. In spite of all benefits we are still today unsure about how secure is actually our data on cloud servers and whether our communication with this server is actually secure. The algorithm proposed in this paper when implemented provides a secure way to communicate and store data in cloud servers.